The butterfly's daughter - Monroe, Mary Alice (Gallery Books, 2011)
Following the migrating monarchs across the United States to Mexico, Luz Avila arrives in San Antonio to find her aunt and meets her mother, who she had always believed dead. Now Luz must face her mother's reappearance in her life and get her grandmother's ashes to Mexico for the Day of the Dead.